The Influence Of Competency, Communication And Work Environment On Employee Performance In Mina Store (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : The purposse of this case is analize influence of competence, communication, work envirunmenntt on the performance of mina store employees Design/Methode/Approach : Used quantitative approach tachniqu used by casuality. The population is 30 employee Mina storeResearch Finding :The differennce from thiscase is that partially environment variables have a significannt effectt on employee performannce but variables competency  work environment do not have a significannt effect on  emplloyee performannce. Simultan, the variable of competency,communinication, work environnment has significant effect on employees mina storeTheoretical contribution/Originality :There have not been many studies that have examined the influennce of comppetence,comuunication and work environnment on performance wealthy peoplePractitionel/Policy implication : Can be used for human Resources development at mina storeResearch limitation : Limitation this case delay in resources the research respondent